A FAST METHOD FOR OPTIMIZING THE K-CLUSTERING BI-CLIQUE COMPLETION PROBLEM IN TELECOMMUNICATION - SALEH, SAGVAN ALI; HIFI, MHAND (Journal of Duhok University, 2017)
In this work, we present a fast approximate method for solving the k-Clustering Minimum Bi-clique Completion Problem (KBCP), a problem belonging to the telecommunication and transportation do- mains. In KBCP, we are given a set of demands of services from customers and its goal is to determine a subset of k multicast sessions that is able to partition the set of the starting demands. Each of the considered service has to belong to a multicast session while each costumer can appear in more sessions. The KBCP is tackled by using a fast approximate method which is based on the principle of neighborhood search techniques. The method can search several solutions belonging to diversified sub-spaces aiming to find the best solution. The performance of the presented method is evaluated on benchmark instances taken from the literature, whereby the provided results are compared to those reached by the Cplex solver and recent methods described in the literature. The results show that, the proposed method is fast and competitive and it is able to reach new bounds.